Особенности работы с рукописными архивными документами (на материале архива Мстислава Добужинского и дневников Ольги Дубенецкене- Калпокене) - Fedorovskaya, Olga (Vilnius University Open Series, 2024)
The article highlights key aspects of working with archival handwritten documents by using the example of the Mstislav Dobuzhinsky Foundation and the diaries of Olga Dubeneckienė-Kalpokienė. The author examines the difficulties associated with deciphering and interpreting such sources, including issues of handwriting, outdated vocabulary, the need for cross-documentary analysis, and the impact of correct reading on researchers’ conclusions. The importance of an integrated approach to the analysis of manuscripts, including the use of digital technologies and artificial intelligence, as well as the role of such research in the field of history and philology, is emphasized.
Keywords: архив; исследования; рукописи; Добужинский; Дубенецкене-Калпокене